Integration of Artificial Intelligence (AI) and Sharia Compliance: Challenges of Smart Contract Implementation in Sharia Fintech Lending Peer-to-Peer (P2P) Products - Syafiul Umam; Ahmad Zainul Abidin; Muhammad Farid Al-Azhar (ISTIFADA : Jurnal Ekonomi dan Lembaga Keuangan Syariah, 2026)
The development of Sharia-based financial technology (fintech) has driven the transformation of financial services through the use of Artificial Intelligence (AI) and smart contracts to improve efficiency, transparency, and accuracy in the financing process. However, the implementation of these two technologies in Sharia Fintech Lending Peer-to-Peer (P2P) products still faces various challenges, particularly in maintaining compliance with Sharia principles. This study aims to analyze the integration of AI and Sharia compliance and identify the challenges of implementing smart contracts in Sharia Fintech Lending P2P products . The study uses a qualitative approach with a library research method strengthened by an analysis of regulations, fatwas from the National Sharia Council-Indonesian Ulema Council (DSN-MUI), provisions of the Financial Services Authority (OJK), and various scientific literature related to AI, blockchain , smart contracts , and Sharia finance. Data analysis was conducted descriptively and analytically through data reduction, categorization, interpretation, and drawing conclusions. The results of the study indicate that AI integration can improve the quality of credit scoring , accelerate the identity verification process ( electronic Know Your Customer/e-KYC ), detect potential financing risks, and strengthen real-time compliance monitoring. On the other hand, the implementation of smart contracts provides benefits in the form of contract automation, operational efficiency, transaction transparency, and reduced risk of default. However, its implementation still faces challenges such as limited flexibility of sharia contracts in digital systems, potential bias of AI algorithms, suboptimal AI governance standards in accordance with sharia principles, issues of personal data protection, and the lack of harmonization of regulations regarding the use of blockchain and smart contracts in the sharia fintech industry in Indonesia. This study concludes that the success of AI and smart contract integration in Sharia P2P Fintech Lending is not only determined by technological sophistication, but also requires strengthening sharia governance ( Sharia Governance ), algorithm transparency ( Explainable AI ), supervision by the Sharia Supervisory Board, and regulatory improvements that are adaptive to developments in digital technology. These findings are expected to serve as a reference for regulators, Sharia fintech industry players, and academics in developing a Sharia digital financial ecosystem that is innovative, secure, and remains in accordance with the principles of maqashid shariah